1994
DOI: 10.1093/clinids/19.6.1045
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Parotitis in Patients with AIDS

Abstract: Adenoviruses are well documented as opportunistic pathogens in patients with immunocompromising conditions, including human immunodeficiency virus (HIV) infection. We recently diagnosed adenovirus infection of the parotid gland in two patients with AIDS. Viral cultures and electron microscopic examinations of parotid tissue were positive in both cases. Adenovirus infection should be considered in the differential diagnosis of parotid swelling in HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Coexisting infections are very seldom reported in the parotid 509 J Oral Pathol Med 30: 507-9 gland of AIDS patients. We found a single report of coinfection of the parotid gland with adenovirus and Mycobacterium aviumintracellulare (6). The patient had advanced HIV infection, low CD4 cell count and had had previous opportunistic infections, similar to the present case.…”
supporting
confidence: 83%
“…Coexisting infections are very seldom reported in the parotid 509 J Oral Pathol Med 30: 507-9 gland of AIDS patients. We found a single report of coinfection of the parotid gland with adenovirus and Mycobacterium aviumintracellulare (6). The patient had advanced HIV infection, low CD4 cell count and had had previous opportunistic infections, similar to the present case.…”
supporting
confidence: 83%
“…Coexisting infections are very seldom reported in the parotid gland of AIDS patients. Currently, there are two reported that showed this association, one of them belonging to our cohort (Vargas et al , 2001) and the other to Gelfand et al (1994). Such manifestations in the parotid gland are probably the result of profound immunosuppression.…”
Section: Discussionmentioning
confidence: 52%
“…asymptomatic) in his right parotid gland and the AdhAQP1 vector transduced some of the cells containing WT Ad5. Adenoviruses can infect parotid glands, although frank clinical manifestations (parotitis) are only reported for immunocompromised patients 11. The presence of an asymptomatic Ad5 infection in this patient might then permit either: (i) a recombination event to occur between the WT Ad5 and AdhAQP1 or (ii) reactivation of the WT Ad5 and subsequent replication of both the WT Ad5 and the AdhAQP1 vector, independently, in the absence of a recombination event.…”
Section: Resultsmentioning
confidence: 95%
“…First, adenoviral infections are quite common across widely diverse populations 12–15, with latent infections present in many organs and in lymphoid tissue 16. Second, the reactivation of latent adenovirus can occur in immunosuppressed patients, such as in post‐transplant or HIV‐AIDS patients 11, 16, 17. Furthermore, in transplant patients, this reactivation appears to be facilitated during antiviral (CMV) prophylaxis with either ganciclovir or valganciclovir 16.…”
Section: Discussionmentioning
confidence: 99%